Development of A Basic English Board Game on Local Culture as An Interactive Learning Media for Elementary Students in Rural Papua - Bawawa, Marni; Purwanti, Ratna; Pertiwi, Sri Ananda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a board game as an interactive English learning media for elementary school students in rural Papua. At the elementary level, English has been mandated as a compulsory subject; however, interest and motivation to learn remain low in the rural regions of Papua. The availability of English teaching media that is relevant to the local context of Papua's children is still limited. This research employed the research and development method with the Plomp model, which includes investigation, design, realization, evaluation and revision, and implementation phases. This study involved 15 elementary indigenous Papuan students and 2 teachers. Validation sheets, learning tests, and interview serve as the research instruments. The data were analyzed using descriptive statistics. The results indicate that the board game is feasible to use as an English introduction media for elementary school students in the rural Papua region, especially South Papua. Media validity tests show a score of 84.25%, while practicality validation indicates 76.5% both are in the high category. Additionally, learning outcomes demonstrate that 80% of students perform at a good level, confirming the media's effectiveness. It can be concluded that the Basic English Board Game is a valid and appropriate tool for introducing English to elementary students in the rural regions of South Papua.